Not my responsibility: The Impact of separate special education systems on educators' attitudes toward inclusion - Gregory, Jess (Educational Policy Analysis and Strategic Research, 2018)
Framed in terms of global policy pressures, this study explored differences in educator attitudes towards the inclusion of children with mild to moderate disabilities in the general education setting in Australia, Barbados, Romania, Turkey, and the United States. The purpose of this study was to investigate how educator attitudes towards the inclusion vary between nations that have disparate forms of special education systems. A sample of 1679 educators was analysed using the Attitudes Towards Teaching All Students (ATTAS-mm) and a triadic model of attitudes. Significant differences were found between nations. In addition to a statistically significant difference in the overall attitude scale, the three subscales: cognitive, affective and behavioural also demonstrated statistically significant differences with moderate effect sizes. These results support the differentiation of professional development for educators dependent on the setting and admonish against policy makers exporting educational policies as best practices regardless of context. (18) Not my responsibility: The Impact of separate special education systems on educators' attitudes toward inclusion. Available from: https://www.researchgate.net/publication/324545240_Not_my_responsibility_The_Impact_of_separate_special_education_systems_on_educators%27_attitudes_toward_inclusion [accessed Apr 24 2018].
7 citations (Crossref) [2023-10-31]
Keywords: dept.edl; peer-reviewed

Fostering meaningful peer interactions: Going beyond the nice - Gregory, Jess (Quick Hits: Teaching tips for adjunct faculty and lecturers, 2015)
Keywords: dept.edl

Instructional scaffolding to promote an autonomous learner - Gregory, Jess L (Preparing Pre-Service Teachers for the Inclusive Classroom, 2017)
An autonomous learner has developed an intrinsic motivation that drives him or her to pursue learning for the inherent satisfaction and enjoyment that stems from the acquisition of knowledge. This chapter presents strategies for teachers to develop a classroom of more autonomous learners. In addition to some strategies and sequencing of activities to maximize their impact, the chapter presents Universal Design for Learning as a framework for thinking about all teaching and ways to apply differentiated instruction to meet the needs of all learners. While there is a focus on the experience of a novice teacher, the content of this chapter is relevant for all educators looking to reinvigorate their practice to empower students to be more in command of their own learning.
Citation Key Alias: lens.org/149-445-063-289-055
Keywords: dept.edl

Trust relationships in schools: supporting or subverting implementation of school-wide initiatives - Gregory, Jess L. (School Leadership & Management, 2017)
This article explores trust relationships in schools that involve disparities in power. Trust is a key factor in developing a positive school culture and strong leadership in schools. Even with the flattening of hierarchies through more distributive models of leadership, disparities in power exist and they influence the trust relationships in schools. Through both French and Raven’s and Follett’s conceptualisations of power, five brief autobiographical stories about trust in schools are deconstructed. Lessons for leadership are gleaned from the power relationships in the autobiographical stories of trust shared by public school educators. In addition, general recommendations are offered that are relevant for all levels of school leadership including but not limited to the instructional coach, the curriculum supervisor, the building principal, and the classroom teacher.
8 citations (Crossref) [2023-10-31]
Keywords: Follett; French & Raven; Trust; change leadership; dept.edl; educational leadership; power

Applying SERVQUAL: Using service quality perceptions to improve student satisfaction and program image - Gregory, Jess L. (Journal of Applied Research in Higher Education, 2019)
Purpose: Austerity approaches in higher education require choosing the highest leverage strategies of increasing student satisfaction. Attending to student perceptions of program/service quality (SERVQUAL) is a means to identify areas that have the greatest return on investment. The paper aims to discuss these issues. Design/methodology/approach: This study explores how a program has applied the SERVQUAL model and survey to identify areas for growth. Findings: The survey of 57 students in a cohort-based doctoral program demonstrated the smallest gaps (highest satisfaction) with the domains of empathy (1.33) and responsiveness (1.30) and the lowest with reliability (2.03), tangibles (1.97) and assurance (1.90). Practical implications: While not all of the five dimensions are within the purview of a program to address (some may require funding that is determined at a college or university level), many of the gaps can be addressed by adopting procedures and policies that increase transparency so that students can moderate their expectations and faculty and staff can provide reliable information. Additionally, the use of the SERVQUAL model provided this program with specific, actionable information that could be used to improve the program. Originality/value: The study includes a review of studies that have applied the SERVQUAL model in higher education. The application of SERVQUAL to a cohort-based doctoral program to identify program improvements and steward program image fits into a gap in the extant literature. © 2019, Emerald Publishing Limited.
14 citations (Crossref) [2023-10-31] tex.ids: lens.org/000-458-242-452-814, pop00269 tex.type: [object Object]
Keywords: Market-driven forces in education; SERVQUAL; Service quality; Student satisfaction; dept.edl; peer-reviewed

Provoking perspectives of creativity and innovation in leadership: innovation, accountability, and the human side of change - Gregory, Jess L (Journal of Leadership Studies, 2016)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/056-562-317-960-189 tex.type: [object Object]
Keywords: dept.edl; peer-reviewed

Lecture is not a dirty word, how to use active lecture to increase student engagement - Gregory, Jess L (The International Journal of Higher Education, 2013)
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/087-594-043-530-106 tex.type: [object Object]
Keywords: dept.edl

Sabbatical leave report. - Gregory, Jess L. (2019)
Sabbatical to write textbook: "School leadership for learning : learning theory to improve professional practice".
Keywords: dept.edl; faculty_collection; sabbatical_report

Constructing Your Dissertation: A Guide for Students as They Begin Their Doctoral Research - Gregory, Jess L. (CreateSpace, 2016)
Keywords: Authorship; Academic writing; Dissertations; Academic; dept.edl; faculty_collection

Case Study 8: The Censorship Crisis: Response 1 - Gregory, Jess L. (Educational Leadership in Action, 2015)
This chapter presents a complex, real-life, accessible case study in expecting the best to provoke and stimulate conversation around practical problems and alternative solutions that confront educational leaders today. These cases cover a wide range of topics, including: teacher evaluations, educational reforms, school safety, cultural differences, undocumented students, and social media. Each case study has three alternative responses written by experienced educational administrators and academics. The respondents were asked to identify the primary problem, along with secondary problems to provide a strategy that will address the problems identified. The chapter starts with an observation that, over time, any supervisor who moves up the chain of responsibility experiences much, and usually begins to formulate empirically derived rules. The organization and unique approach of Educational Leadership in Action allows for flexible use in courses for aspiring leaders to supplement core readings, reinforce central concepts, exemplify theory, and provide grounded examples to encourage learning.
Num Pages: 1
Keywords: dept.edl

Revalidating an instrument to gain insights into changing attitudes towards teaching all students - Gregory, Jess; Noto, Lori (NERA Conference Proceedings 2019, 2019)

Crisis of credibility - Vigliotti, Darron; Gregory, Jess L (Journal of Leadership Studies, 2013)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/058-561-442-490-372 tex.type: [object Object]
Keywords: dept.edl; peer-reviewed

Mindfulness as a prerequisite to effective leadership; exploring the constructs that foster productive use of feedback for professional learning - Day, Danette V; Gregory, Jess L (Interchange, 2017)
This paper proposes a model that integrates mindfulness, ego, and mindset as filters of the information available for professional learning. The paper explores connections between mindset, ego, and mindfulness that promote or inhibit an educator’s ability to use feedback for learning. A leader’s commitment to creating spaces for meaningful use of all types of feedback promotes a school climate that encourages risk taking in learning. Mindfulness, the cultivation of the ability to pay attention to the present moment non-judgmentally, is a prerequisite skill to the effective delivery and use of feedback to promote professional learning. The development of mindfulness requires practice of a method and the continual application of mindfulness to remain open to learning from feedback. © 2017, Springer Science+Business Media B.V.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-616-943-494-687 tex.type: [object Object]
Keywords: Effective leadership; Ego; Feedback; Mindfulness; Mindset; Professional learning; dept.edl

Attitudinal instrument development: Assessing cognitive, affective, and behavioral domains of teacher attitudes toward teaching all students - Gregory, Jess L; Noto, Lori A (Cogent Education, 2018)
Despite their entree into the physical space of general education classrooms and the expected instruction of the core academic standards, students with disabilities may still be excluded. Successful inclusion requires a commitment at district, school and classroom level. The attitude of the general education teacher toward the inclusion of students with disabilities is a critical component in the success of inclusionary efforts. The attitudes toward teaching all students (ATTAS-mm) instrument are a nine-item scale with strong reliability and validity that measures educator attitudes. The three subscales: believing all students can succeed in general education classrooms (cognitive), developing personal and professional relationships (affective), and creating an accepting environment for all students to learn (behavioral) explain nearly 80% of the variance in scores. The unstandardized Cronbach alpha for the entire ATTAS-mm scale was 0.83. The three subscales also demonstrated acceptable reliability values (Cognitive, 0.72; Affective, 0.93; Behavioral, 0.84). With strong internal reliability and validity established through a panel of experts and alignment with cognitive psychology literature, the ATTAS-mm was determined to be a valid and reliable instrument for measuring the attitudes toward teaching all students. © 2018 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/178-902-357-221-200 tex.type: [object Object]
Keywords: ATTAS-mm; dept.edl; inclusion; instrument development; peer-reviewed; special education; teacher attitudes

Exploring the use of faded worked examples as a problem solving approach for underprepared students - Hesser, Tiffany L; Gregory, Jess L (Higher Education Studies, 2015)
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-486-092-947-358 tex.type: [object Object]
Keywords: dept.edl

Efficacy of Mindfulness in the Classroom - DeLuca, Suzanne; Gregory, Jess; Day, Danette (European Journal of Applied Positive Psychology, 2018)
This article contextualizes mindfulness and examines a portion of the literature on mindfulness based interventions in the classroom. Mindfulness or the result of intentional, moment-tomoment awareness in a kind and discerning way can be cultivated with practice. There are many different mindfulness practices which can be utilized in a classroom environment. Some of the popular mindfulness practices are grounded in Kabat-Zinn’s Mindfulness Based Stress Reduction program which incorporates sitting meditation, mindful yoga, mindful eating and the body scan. Mindfulness practices can be modified to fit the classroom setting and the grade level of students. With a growth in the number of studies involving mindfulness in the classroom this article explores the question of its efficacy with children and seeks to answer the question: is mindfulness in the classroom effective and what are the studies reporting?
Keywords: dept.edl; peer-reviewed; ⛔ No DOI found

Using educator characteristics on attitudes toward inclusion to drive professional development - Gregory, Jess L.; McCoy, T.; Baker, M.; Fedigan, A. (Journal of Advances in Education Research, 2016)
Keywords: dept.edl

Attitudes of Croatian and Polish elementary school teachers towards inclusive education of children with disabilities - Cwirynkalo, Katarzyna; Kisovarivanda, Tamara; Gregory, Jess L; Żyta, Agnieszka; Arciszewska, Aleksandra; Zrilic, Smiljana (Hrvatska Revija za Rehabilitacijska Istraživanja, 2017)
Inclusive education has been gaining increasing attention from governments throughout the world. Croatia and Poland, two European Union members that ratified the Convention on the Rights of Persons with Disabilities, have been working on issues related to improving the quality of education of children with special educational needs. The aim of this article was to explore the attitudes of Croatian and Polish elementary education teachers towards inclusion of these children in regular classes. The sample consisted of 98 elementary education teachers from Croatia (N=50) and Poland (N=48). A diagnostic survey based on the Teacher Attitudes Toward Inclusion Scale (TATIS) (Cullen, Gregory, & Noto, 2010) was used. The instrument allows measurement of three main components of attitudes: teacher perceptions of students with mild to moderate disabilities (POS), their beliefs about the efficacy of inclusion (BEI), perceptions of professional roles and functions (PRF), as well as their general attitudes towards inclusion. We found that Polish teachers received significantly higher scores on two subscales: POS and BEI. We also found that age and place of living influenced the attitudes of teachers in the two groups. Implications for practice are discussed. © 2017, University of Zagreb, Faculty of Political Sciences. All rights reserved.
Citation Key Alias: lens.org/154-714-360-054-192 tex.type: [object Object]
Keywords: Children with disabilities; Inclusive education; Teachers’ attitudes; dept.edl; ⛔ No DOI found

Culturally responsive practice and the role of school administrators - Minkos, Marlena L.; Sassu, Kari A.; Gregory, Jess L.; Patwa, Shamim S.; Theodore, Lea A.; Femc-Bagwell, Michele (Psychology in the Schools, 2017)
In recent years, student populations within public schools in the United States have become increasingly diverse, both culturally and linguistically, and are projected to continue to grow in diversity in the future. Consequently, educators must be prepared to support the needs and education of students with multicultural backgrounds who may differ from them. School administrators play an important role in creating safe, accepting school environments and guiding the education of diverse student populations. However, there is a need for additional guidance for school leaders in cultivating schools that promote equity for all students. Using the National Policy Board for Educational Administration (NPBEA) Professional Standards for Educational Leaders as a guiding framework, this paper provides practical suggestions regarding culturally responsive strategies and practices that school administrators might employ in leading diverse school communities.
15 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000415935300007, lens.org/072-893-262-948-380 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: culturally responsive practice; dept.csp; dept.edl; diversity; educational leadership; peer-reviewed